2020
DOI: 10.1111/1462-2920.15223
|View full text |Cite
|
Sign up to set email alerts
|

Fungal volatiles mediate cheese rind microbiome assembly

Abstract: Summary In vitro studies in plant, soil, and human systems have shown that microbial volatiles can mediate microbe–microbe or microbe–host interactions. These previous studies have often used artificially high concentrations of volatiles compared to in situ systems and have not demonstrated the roles volatiles play in mediating community‐level dynamics. We used the notoriously volatile cheese rind microbiome to identify bacteria responsive to volatiles produced by five widespread cheese fungi. Vibrio casei had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 85 publications
3
33
0
Order By: Relevance
“…Apart from soluble SM, volatile organic compounds (VOCs) are as well capable of impacting a microbial community. In 2020, Cosetta et al demonstrated that VOCs of cheese rind-associated fungi have both growth-stimulating and -inhibiting properties on members of the rind microbiome [60]. The authors could reveal that the VOC-mediated shift of the bacterial community was caused due to growth promotion of Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from soluble SM, volatile organic compounds (VOCs) are as well capable of impacting a microbial community. In 2020, Cosetta et al demonstrated that VOCs of cheese rind-associated fungi have both growth-stimulating and -inhibiting properties on members of the rind microbiome [60]. The authors could reveal that the VOC-mediated shift of the bacterial community was caused due to growth promotion of Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side of the spectrum, in raw milk cheeses produced with no starter or by using traditional undefined starters, and with longer ripening, a complex pattern of microbial interactions and a succession of species and strains invariably develops and its control is key to cheese quality (Blaya et al, 2017; Gobbetti et al, 2018; Irlinger and Mounier, 2009; Jonnala et al, 2018; Mayo et al, 2021). Microbial successions and interactions are especially complex in surface ripened cheeses (Irlinger and Mounier, 2009), and this has been demonstrated in an elegant and comprehensive way in a series of recent studies (Bonham et al, 2017; Cosetta et al, 2020; Kastman et al, 2016; Niccum et al, 2020; Wolfe et al, 2014; Zhang et al, 2018).…”
Section: Forewordmentioning
confidence: 99%
“…The collection and interpretation of multi-omic data is probably the most promising approach for the study of microbial interactions in cheese during curd production and ripening, although cost and computational power issues may still limit the collection of large longitudinal data sets needed to use model based approaches for inferring interactions. The most extensive demonstration of the value of complex, integrated approaches, for finely dissecting the complex interactions in cheese microbial communities is probably the on-going work on surface ripened cheeses (Bonham et al, 2017; Cleary et al, 2018; Cosetta and Wolfe, 2020; Cosetta et al, 2020; Kastman et al, 2016; Niccum et al, 2020; Wolfe et al, 2014; Zhang et al, 2018). Starting from an extensive metataxonomic and metagenomic characterization of the rind microbial communities of bloomy surface, washed rind and natural dry rind (Wolfe et al, 2014) from all over the world, and from the development of a detailed set of protocols for dissecting interactions in model cheeses (Cosetta and Wolfe, 2020), this group was able to provide detailed evidence for the drivers which determine the diversity and functionality of microbial communities on the surface of cheeses.…”
Section: Network Analysis Concepts and Approaches To The Study Of Microbiotamentioning
confidence: 99%
“…The authors could reveal that the VOC-mediated shift of the bacterial community was caused due to growth promotion of Vibrio spp. [60]. These studies and the results from the semi-synthetic mock community experiment of this study highlight that the overall impact of SMs on the targeted microbial communities is low, which suggest being no mass destruction compounds.…”
Section: Discussionmentioning
confidence: 58%